Disordered Memory and Fragmented Narration in William Faulkner’s The Sound and the Fury (1929) - BENTIRECHE, Nadhir; KHALFA, Sayeh (Faculty of Letters and Foreign Languages Department of English, 2018)
Each literary era claims a unique style and philosophy of literature, to which many authors ascribe. William Faulkner is a well-known American writer whose fiction stands for literary modernism. The present dissertation examines the literary modern experimentation in William Faulkner’s novel The Sound and the Fury (1929). Accordingly, the purpose of this research is to study the modern narrative techniques employed by Faulkner to achieve this experimentation with time and narrative devices. More accurately, this research seeks to investigate the use of disordered memory as well as fragmented narration in the studied novel. This investigation suggests that the use of different modernist techniques such as stream of consciousness, multiple point of views, fragmentation, and non-chronological time all serve Faulkner to achieve his goal of presenting a highly modernist novel. Additionally, to better achieve his innovative techniques, Faulkner uses two radically different narrators. The first narrator is mentally disabled and has poor cognitive skills that affect both his language and comprehension of time. The second narrator is highly educated and uses sophisticated language and who develops an obsession with time. Ultimately, disordered memory and fragmented narration are both employed effectively in Faulkner’s novel The Sound and the Fury.